American Music in Wind Band Repertoire: the Importance and Need for Heritage Preservation - (:unkn) unknown (My University, 2017)
For an instrumental conductor in a music education program, repertoire selection is an important step while preparing for a concert program. Choosing quality music that represents varied genres, styles, and historical periods helps to create a stimulating concert for the listeners and a well-balanced musical preparation for the player. Performing music from other countries is essential and should be balanced with American music, specifically folk songs and marches. The purpose of this thesis is to show the placement and benefit, according to composers and arrangers, of utilizing American music within the music classroom, specifically in the choice of wind band repertoire. This qualitative study features five interviews with modern composers and arrangers, musical analysis of two scores, and the compilation of a repertoire database for American folk songs and marches. The three main research questions that guided this process were: 1) what is the accessibility of folk songs and marches in wind band repertoire, 2) why is the heritage of these categories important in the modern-day classroom, and 3) what musical elements contribute to traditional American music. Triangulation of the data helped demonstrate that distinguishing elements found in marches and folk songs are indicators of the musical heritage of the United States. The interviewees outlined musical components that are found in works defined as American music, how pieces belong to this category and notable past composers. The musical analyses outlined two chosen works, Shenandoah and The Stars and Stripes Forever, which includes detailed information about melody, accompaniment, form, articulation, and other performance practices employed in North American folk songs and marches. A reference database of folk songs and marches is included as a tool for educators to utilize when programming specifically for these categories of music.